2012
DOI: 10.1080/15287394.2012.690705
|View full text |Cite
|
Sign up to set email alerts
|

Metal(Loid) Levels in Biological Matrices from Human Populations Exposed to Mining Contamination—Panasqueira Mine (Portugal)

Abstract: Mining activities may affect the health of miners and communities living near mining sites, and these health effects may persist even when the mine is abandoned. During mining processes various toxic wastes are produced and released into the surrounding environment, resulting in contamination of air, drinking water, rivers, plants, and soils. In a geochemical sampling campaign undertaken in the Panasqueira Mine area of central Portugal, an anomalous distribution of several metals and arsenic (As) was identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 44 publications
2
38
0
2
Order By: Relevance
“…Present findings are also consistent with preliminary studies (Coelho et al, 2011;Coelho et al, 2012) pointing to increased genotoxic damage experienced by populations environmentally and occupationally exposed to metal(loid) contamination derived from the Panasqueira mine activities. To strengthen the absence of causal association between mine activities and this damage, the level of most biomarkers was quantitatively associated with the intensity of genotoxic exposure.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Present findings are also consistent with preliminary studies (Coelho et al, 2011;Coelho et al, 2012) pointing to increased genotoxic damage experienced by populations environmentally and occupationally exposed to metal(loid) contamination derived from the Panasqueira mine activities. To strengthen the absence of causal association between mine activities and this damage, the level of most biomarkers was quantitatively associated with the intensity of genotoxic exposure.…”
Section: Discussionsupporting
confidence: 94%
“…These findings were implemented by biomonitoring studies which found higher concentrations of metal(loid)s, such as As, Cr, Mn, Mo, Pb and Zn in the blood, urine, nails, and hair of people living near or working in the mine (Coelho et al, in press). Preliminary data showing increased genotoxic damage in these populations are also available (Coelho et al, 2011(Coelho et al, , 2012. The present study with a more robust design was aimed to evaluate the genotoxic damage caused by this contamination and the possible influence of a set of genetic polymorphisms.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Approximately 2 × 10 7 ha of arable land in China has been contaminated with heavy metals such as arsenic (As), cadmium (Cd), chromium (Cr), lead (Pb), and zinc (Zn) to various degrees, due to local mining and refinery activities (Li, 2005). Accumulation of heavy metals in soils and sediments not only affects soil fertility, crop yield, and quality of agriculture products, but also negatively impacts human and animal health by entering the food chain (Coelho et al, 2012;Dahshan et al, 2013;Figueiredo et al, 2014aFigueiredo et al, , 2014b.…”
mentioning
confidence: 99%
“…As far as exposure is concerned, the most important matter of current publications is drinking water pollution (Maity et al 2012;Deb et al 2012;Guha Mazumder et al 2012;Marchiset-Ferlay et al 2012;Chen et al 2012;Kumasaka et al 2013). Another contemporary issue coming into focus is environmental contamination from (former) mining activities (Coelho et al 2012;Li et al 2012;Chakraborti et al 2012) and from waste deposits (Moreno-Santini et al 2012).…”
mentioning
confidence: 99%